Management of pediatric facial fractures during COVID-19 pandemic - Abramowicz, Shelly (Oral Surg Oral Med Oral Pathol Oral Radiol, 2021)
OBJECTIVE: The coronavirus disease 2019 (COVID-19) pandemic caused delays in medical and surgical interventions in most health care systems worldwide. Oral and maxillofacial surgeons (OMSs) delayed operations to protect themselves, patients, and staff. This article (1) presents one institution's experience in the management of pediatric craniomaxillofacial trauma during the COVID-19 pandemic and (2) suggests recommendations to decrease transmission. METHODS: This was a retrospective review of children aged 18 years or younger who underwent surgery at Children's Healthcare of Atlanta in Atlanta, GA, between March and August 2020. Patients (1) were aged 18 years old or younger, (2) had one or more maxillofacial fractures, and (3) underwent surgery performed by an OMS, otolaryngologist, or plastic surgeon. Medical records were reviewed regarding (1) fracture location, (2) COVID-19 status, (3) timing, (4) personal protective equipment, and (5) infection status. Descriptive statistics were computed. RESULTS: Fifty-eight children met the inclusion criteria. The most commonly injured maxillofacial location was the nose. Operations were performed 50.9 hours after admission. Specific prevention perioperative guidelines were used with all patients, with no transmission occurring from a patient to a health care worker. CONCLUSIONS: With application of our recommendations, there was no transmission to health care workers. We hope that these guidelines will assist OMSs during the COVID-19 pandemic.